MEMULIHKAN JIWA DITENGAH KESIBUKAN : PERAN PASTORAL KONSELING BAGI PEKERJA DI UPTD PPA SULAWESI UTARA - Raintung, Agnes B.J; Lokong, Yolanda Mega Ritme; Palar, Dennis (PT. Giat Konseling Nusantara, 2025)
This article discusses the role of pastoral counseling in the effort to restore the souls of workers at UPTD PPA North Sulawesi who face various psychological and spiritual challenges in carrying out their duties. This research employs a qualitative method with a descriptive approach through in-depth interviews with workers. The results show that workers face various challenges such as high workload, exposure to secondary trauma, security risks, and ethical dilemmas that significantly impact their mental health. Pastoral counseling emerges as an approach that integrates spiritual dimensions with psychological recovery, providing holistic support that encompasses emotional and spiritual aspects. Through the pastoral counseling approach, workers can find deeper meaning in their work, build spiritual resilience, and manage stress more effectively. This research provides important insights into how pastoral counseling can play a role in restoring and maintaining the mental health of workers amid challenging work demands.